Envolvimento dos sistemas serotoninérgico e dopaminérgico na ação do tipo antidepressiva do 7-flúor-1,3 difenilisoquinolina-1-amino em camundongos - Pesarico, Ana Paula (2014)
Depression is a psychiatric disorder associated with a negative impact on quality of life. Monoaminergic system has been involved in this disease and in the action of antidepressants. This study aimed to investigate the potential antidepressant-like of 7-fluoro-1,3-diphenylisoquinoline-1-amine (FDPI) and the possible involvement of monoaminergic system. Results showed that FDPI (1, 10 and 20 mg/kg, intragastric (i.g.)) reduced the immobility time, increased swimming time, but did not alter climbing time of mice in the modified forced swimming test (FST). These effects were similar to those of paroxetine (8 mg/kg, intraperitoneally (i.p.)), a selective serotonin reuptake inhibitor, which was used as positive control. Pretreatments with p-chlorophenylalanine (pCPA, an inhibitor of serotonin (5-HT) synthesis, 100 mg/kg, i.p., once a day for 4 consecutive days), N-[1]-N-(2-pyridinyl) cyclohexanecarboxamide (WAY 100635, a 5-HT1A receptor antagonist, 0.1 mg/kg, subcutaneous injection (s.c.)) and ondansetron (a 5-HT3 receptor antagonist, 1 mg/kg, i.p.) reversed the antidepressant-like effect of FDPI at the dose 1 mg/kg in FST, this did not occurs with ritanserin (a 5-HT2A/2C receptor antagonist, 1 mg/kg, i.p.). Antagonist related with dopaminergic system, as haloperidol (a D2 receptor antagonist, 0.2 mg/kg, i.p.) and SCH23390 (a D1 receptor antagonist, 0.05 mg/kg, s.c.) were able to reverse the antidepressant-like effect of FDPI at the dose 1 mg/kg in FST, this did not occurs with sulpiride (a D2 and D3 receptors antagonist, 50 mg/kg, i.p.). FDPI, at doses of 10 and 20 mg/kg, inhibited monoamine oxidase-B activity in prefrontal cortex of mice. These results suggest that FDPI produced an antidepressant-like action in the FST in mice, possibly by an involvement of the monoaminergic system. Additional studies are necessary in order to propose FDPI as a drug for depression treatment.